The Role of Remote Sensing and GIS in Monitoring the Impact of Green Areas on Temperatures and Improving the Quality of Life in Dammam City - M. Alamri, Nourah (Journal of Posthumanism, 2025)
Climate change emerges as one of the most significant challenges facing the world, prompting various plans to mitigate its causes and minimize its effects. The Kingdom of Saudi Arabia has pursued this through numerous initiatives outlined in Vision 2030 and other development plans, aiming to achieve the Sustainable Development Goals, particularly those related to quality of life, the environment, and climate. Dammam, in the Eastern Province, is a key city in the Kingdom, serving as the region’s petroleum production hub and a major industrial center. Variations in land use due to urban and industrial activities in cities create notable environmental challenges, particularly the formation of heat islands, especially those resulting from industrial activities. This impacts urban quality of life. Therefore, the use of remote sensing and Geographic Information Systems (GIS) technologies is crucial for monitoring, analyzing, and evaluating the Kingdom’s projects aimed at reducing local temperatures through urban planning, including afforestation and increasing green spaces.This study relied on Landsat satellite imagery to monitor vegetation cover changes and surface temperature distributions between (2014:2024). Indicators such as the Normalized Difference Vegetation Index (NDVI) and Land Surface Temperature (LST), along with per capita green space, were used to assess the relationship between vegetation density, temperatures, and quality of life in industrial and urban areas of Dammam. The goal was to conduct a spatial assessment of the impact and effectiveness of green space and vegetation projects in mitigating thermal effects in the city and its surrounding areas.The results highlight the importance of integrating remote sensing and GIS technologies in environmental planning and monitoring climate impacts in cities with dense urban and industrial activities. The study also demonstrates that afforestation and increasing green spaces contribute significantly to reducing temperatures in surrounding areas, particularly industrial zones, and major roads, thereby strengthening their role as sustainable environmental solutions. This reinforces the recommendation to expand afforestation and green spaces as part of environmental and climate policies that enhance the quality of life in Dammam and achieve the goals of the Kingdom’s Quality of Life Document in accordance with Vision 2030.